A network meta-analysis of mind–body exercise interventions for internet addiction symptoms in young adults - Shiguan Jia; Zhihao Du; Dengshan Chu; Jiayi Yao; Haozhe Wang; Wenjia Chen; Dazhong Zhang; Xin Zang (Frontiers in Public Health)
BackgroundInternet Addiction Disorder (IAD) is a recurrent mental illness. It severely impacts both physical and mental health, leading to physiological symptoms such as neurological dysfunction and immunosuppression. This condition significantly affects adolescent development and has become a global public health concern. Scientific evidence supports the beneficial impact of integrative mind–body exercises for treating internet addiction disorders. Though these interventions show promise, their therapeutic efficacy exhibits considerable variation across different modalities. Currently, there exists a significant research gap, as no comprehensive clinical investigations have systematically evaluated the comparative therapeutic outcomes of distinct mind–body practices among individuals diagnosed with internet addiction.ObjectiveTo conduct a network meta-analytic investigation comparing the therapeutic efficacy of diverse mind–body exercise interventions for addressing symptoms associated with internet addiction disorder.MethodsData were retrieved from Web of Science, PubMed, CNKI, and VIP databases. After screening and data extraction, network meta-analysis was performed using STATA 18.0.ResultsTwenty-four studies were included in the analysis. Compared with the control group (Placebo), Mindfulness [SMD = 13.33, 95%CI (7.42,19.25), p < 0.05] and Taichi [SMD = −10.91, 95%CI (−18.71,−3.11), p < 0.05] significantly improved internet addiction symptoms. According to SUCRA values, the interventions were ranked in order of effectiveness: Mindfulness (SUCRA = 76.3%), DanceSport (SUCRA = 64.0%), Yoga (SUCRA = 63.1%), and Taichi (SUCRA = 62.6%).ConclusionMindfulness and Tai Chi significantly reduce and alleviate internet addiction symptoms compared to Placebo. Based on SUCRA rankings, Mindfulness, Dance Sport, Yoga, and Tai Chi show the highest probability of effectiveness in descending order, providing promising options for managing internet addiction symptoms in young adults.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025631096.